Venous Thromboembolism in Critically Ill Children - Polikoff, Lee A. (2014)
PURPOSE OF REVIEW: To review the current literature on venous thromboembolism in critically ill children RECENT FINDINGS: There is increasing concern for venous thromboembolism and its complications in critically ill children. Critically ill children are at increased risk of thromboembolism because of the treatment that they are receiving and their underlying condition. A complex relationship exists between thrombosis and infection. A thrombus is a nidus for infection while infection increases the risk of thrombosis. Pediatric-specific guidelines for the prevention and treatment of thromboembolism are lacking. Current guidelines are based on data from adults. Novel anticoagulants are now available for use in adults. Studies are ongoing to determine their safety in children. Risk assessment tools have recently been developed to determine the risk of thromboembolism in critically ill children. Certain molecules are associated with thromboembolism in adults. SUMMARY: Pediatric critical care practitioners should be cognizant of the importance of venous thromboembolism in critically ill children to allow for early identification and treatment. Adequately powered clinical trials are critically needed to generate evidence that will guide the treatment and prevention of thromboembolism in critically ill children. Risk assessment tools that incorporate biomarkers may improve our ability to predict the occurrence of thromboembolism in critically ill children.